Changing look active galactic nuclei in the MaNGA survey. Issue 1 (7th July 2020) - Hon, Wei Jeat; Webster, Rachel; Wolf, Christian
ABSTRACT: Changing look active galactic nuclei (CLAGNs) are rare cases of AGNs, where the continuum flux increases/decreases and the broad emission lines appear/disappear within short time-scales. These extreme changes challenge our understanding of accretion disc dynamics. We present a sample of four new CLAGNs at 0.026 < z < 0.107, which were found by cross-matching the Mapping Nearby Galaxies at Apache Point Observatory (MaNGA) survey with AGNs from the SDSS spectroscopic data base. Our results show that the selection criteria of $\gt \mathopen |0.5\mathclose |$  mag change in SDSS- g band is ineffective at lower redshifts. This is, in part, due to the fact that the g band is probing a different part of the AGNs spectral energy distribution at these redshifts. The bigger issue is that the galaxy continuum dominates the spectrum and thus overwhelms any variation of the AGNs continuum that might contribute to photometric variations. This suggests the need to use different methods for future low-redshift CLAGNs searches.